The Dynamics of Macrophage Function in Reparation of Natural Immune System in Tuberculosis Disease - Christina Destri; Jusak Nugraha; Muhammad Amin; Djoko Agus Purwanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Macrophages related with pathogen was involved the ability of Mycobacterium tuberculosis (Mtb) to developing mechanisms to prevent macrophage attacks and the aim of this study was to find the relationship between specific role of macrophages in natural immune system in tuberculosis (TB) disease. The research design of this study used literature reviews from various journals and it was accessed in Google Scholar and various medical science websites who bublessed less than 10 years. Localization of mycobacteria in granulomas form and activation of macrophages ability to kill and eliminate pathogens also the movement of M1 to M2 polarization as an important part for the host to prevent widespread tissue damage. However, the loss of the immune system suppression by M1 and Th1 molecules will give benefit to fertility development of Mtb in the environment of immunity M2 / Th2. The results of this study showed that the dynamics of macrophages in tuberculosis disease is a balance of Mtb’s ability to escape from the immune system. The effectiveness of anti-TB treatment repair the immune system and eliminate Mtb